Management of aging assets in power distribution systems: A comprehensive review - Shaghaghi, Aidin; Taghitahooneh, Mohammad; Yahyaeifar, Mohammad; Dashti, Reza (Energy strategy reviews, 2024)
This article provides a comprehensive framework for the studies of aged assets. All the studies conducted until the end of 2023 in managing aged assets have been summarized and categorized in the framework and model proposed in this article. The proposed comprehensive framework model shows research gaps and a road map can be developed. Aging asset management studies are categorized into aging detection, utilization of aging assets, resilience of asset life, outages caused by aging assets, and operator. This way, we can focus on the methods and applied studies subjects in each sub-section separately. The collection of studies and articles in this paper has been conducted using the Scopus database, and at the end, bibliometric maps are provided. •Providing a comprehensive framework for managing aging assets in power distribution networks.•This paper discusses research gaps and provides a roadmap for future studies on aging assets in power distribution companies.•This article helps in understanding the previous studies by providing a bibliographic model for depreciated assets.•By using the framework proposed in this paper, electric power distribution companies can gain a deep understanding of the aging asset analysis steps and make more optimal decisions.•Consequently, this paper begins by introducing the different types of scheduling in power distribution systems, followed by a detailed presentation of each scheduling aspect.